2016
DOI: 10.12974/2313-0954.2016.03.01.6
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Clinical Trial of Multimodal Therapy and Mulligan’s Concept of Manual Therapy for Patients with Chronic Pain Syndrome Caused by Upper Cervical Spine Disorders

Abstract: Study Design: A randomized, parallel-group clinical trial, 2 weeks treatment period with follow-up reassessment after therapy. Objectives: To compare the relative efficacy of multimodal rehabilitation and Mulligan’s concept of manual therapy for patients with chronic neck pain and cervicogenic headache. Background: Cervicogenic headache and neck pain are the main syndromes caused by upper cervical musculosceletal disorders (C0-C3). According to clinical researches for about 20% of the patients with chronic uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
2
0
2
Order By: Relevance
“…Therefore, in contrast of other studies [50], we conducted a series of sessions avoiding of single intervention protocol, to increase the possible therapeutic impact and reinforce generalizability of clinical indings. A number of nine session or more have been investigated in other studies with positive results [40,51]. Our study design based on the concept of Mulligan therapy effect incorporating all three main components of SNAG/self-SNAG and NAG identi ied the total clinical impact, against a control group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, in contrast of other studies [50], we conducted a series of sessions avoiding of single intervention protocol, to increase the possible therapeutic impact and reinforce generalizability of clinical indings. A number of nine session or more have been investigated in other studies with positive results [40,51]. Our study design based on the concept of Mulligan therapy effect incorporating all three main components of SNAG/self-SNAG and NAG identi ied the total clinical impact, against a control group.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, control group incorporated in study design to limit confounding factors arising from natural history of pain. Put et al showed that Mulligan was superior in terms of ROM [51], comparing with a multimodal therapy consisting of cervical spine massage, electrotherapy and ultrasound in headache patients. Hussain et al, found superiority of NAGS opposite Maitland mobilization in neck patient's measurements of NPRS and NDI, after a fourweek period therapy with a frequency of four session per week [59].…”
Section: Discussionmentioning
confidence: 99%
“…Dentro do tratamento de cervicalgias, os NAGS são deslizamentos acessórios apofisários naturais aplicados à coluna cervical sem movimento ativo do paciente. Já os SNAGS são deslizamentos acessórios apofisários naturais sustentados pelos quais o paciente tenta mover ativamente uma articulação dolorida ou rígida em sua amplitude de movimento, enquanto o terapeuta realiza um deslizamento acessório paralelo ao plano de tratamento (PUT M, et al, 2016).…”
Section: Introductionunclassified
“…A técnica de self-SNAGS é importante para um auto gerenciamento terapêutico do próprio paciente com cervicalgia, pois o movimento ativo é executado com o deslizamento mantido nas facetas articulares, como recurso pode-se usar uma faixa self-SNAG, ou toalha, precisando de um profissional apenas para orientações e prescrição das séries (PUT M, et al, 2016;GAUTAM R, et al, 2014).…”
Section: Introductionunclassified